2020
DOI: 10.21037/gs-20-811
|View full text |Cite
|
Sign up to set email alerts
|

Detection and analysis of multiple biomarkers in ovarian cancer: clinical significance in diagnosis, treatment, and prognosis evaluation

Abstract: Background: The purpose of this study was to explore the clinical significance of CA125, CK7, CK20, ER, PR, C-erbb2, and P-gp in ovarian cancer.Methods: Ovarian cancer patients were recruited from Nantong Cancer Hospital between March 2006 and July 2011. The expressions of CA125, CK7, CK20, ER, PR, C-erbb2, and P-gp were determined by immunohistochemistry (IHC).The chi-square test (χ 2 ) was used to analyze the correlation between each index and the clinical characteristics of the patients. The patients were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
(29 reference statements)
0
1
0
1
Order By: Relevance
“…Among the mentioned OC tumor markers, CK7 and CA125 have the highest positive rate in malignant OC tissues compared with benign ovarian cancer tissues. Studies also shown that patients with negative expressions of CA125 and CK7 had significantly longer recurrence- free survival (RFS) time than those with positive expressions [ 44 ]. Thus, using CA125 and CK7 as malignant OC marker was practical for early diagnosis and lineage determination.…”
Section: Discussionmentioning
confidence: 99%
“…Among the mentioned OC tumor markers, CK7 and CA125 have the highest positive rate in malignant OC tissues compared with benign ovarian cancer tissues. Studies also shown that patients with negative expressions of CA125 and CK7 had significantly longer recurrence- free survival (RFS) time than those with positive expressions [ 44 ]. Thus, using CA125 and CK7 as malignant OC marker was practical for early diagnosis and lineage determination.…”
Section: Discussionmentioning
confidence: 99%
“…У диференційній діагностиці для верифікації первинних муцинозних пухлин яєчників та метастазуючих муцинозних пухлин товстої кишки в тканину яєчника використовуються ЦКР 7, ЦКР 20, CDX2, MUC5AC та вілін [24,25]. ЦКР 7 експресується усіма типами пухлин яєчників, включаючи муцинозні, які також мають позитивну реакцію до ЦКР 20, віліну, у той же час CDX-2 має негативну реакцію (рис.1).…”
Section: імуногістохімічні особливості раку яєчників ім нікітіна тв к...unclassified